2009
DOI: 10.4084/mjhid.2009.004
|View full text |Cite
|
Sign up to set email alerts
|

Thalassaemia Intermedia: an Update

Abstract: Our understanding of the molecular and pathophysiological mechanisms underlying the disease process in patients with thalassaemia intermedia (TI) has substantially increased over the past decade. TI encompasses a wide clinical spectrum of beta-thalassaemia phenotypes. Some TI patients are asymptomatic until adult life, whereas others are symptomatic from as young as 2 years of age. A number of clinical complications commonly associated with TI are rarely seen in thalassaemia major, including extramedullary hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 65 publications
3
45
0
Order By: Relevance
“…Approximately 5-10% of patients live without requiring periodic blood transfusions and are said to have thalassemia intermedia. 3 These two forms of the disease are the extreme ends of a broad range of clinical variability: patients might need to start transfusions after days, months or even years of life, demonstration of a great variation in disease severity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 5-10% of patients live without requiring periodic blood transfusions and are said to have thalassemia intermedia. 3 These two forms of the disease are the extreme ends of a broad range of clinical variability: patients might need to start transfusions after days, months or even years of life, demonstration of a great variation in disease severity.…”
Section: Resultsmentioning
confidence: 99%
“…11 Thalassemia intermedia patients were defined as patients who had never been transfused, or had only been transfused sporadically during infections or surgery (<10 blood units in total). 3 The β-thalassemia mutations were of HBB:c118C>T/HBB:c118C>T type in 92.4% of cases and HBB:c118C>T/HBB:c.20delA type in 6.3% of the studied sample; the remaining mutations are reported in Table 1. The continuous distribution of the phenotypic severity among thalassemia patients was measured by the time at which they started transfusion therapy.…”
Section: Patients and Phenotypic Assessmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Four (5.5 %) patients had evidence of EMH including one with an intradural mass in the D 12 region presenting with features of spinal cord compression and another patient had a mass in the urinary bladder presenting with frank hematuria. Ineffective red cell production by the bone marrow (ineffective erythropoiesis) forces expansion of the hematopoietic tissue outside the marrow medulla and leads to hematopoietic compensatory involvement, mostly in the form of masses, of other regions in the body-the phenomenon termed extramedullary hematopoiesis [18]. Olivieri et al [19] in a review of 109 patients with Ebthalassemia, reported only one patient had a fracture occurred without significant trauma and severe facial deformity was observed in only two patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is now established that such clinical phenotypes lie in severity between those of thalassemia minor (clinically silent, mildly hypochromic, and microcytic anemia) and transfusion-dependent thalassemia major (TM), although there is substantial clinical overlap between the 3 conditions. 3 Three main factors are responsible for the clinical sequelae of TI: ineffective erythropoiesis, chronic anemia, and iron overload. 3 The degree of ineffective erythropoiesis is the primary determinant of the development of anemia, whereas peripheral hemolysis of mature red blood cells (RBCs) remains secondary.…”
Section: Introductionmentioning
confidence: 99%